Dietary magnesium requirement of juvenile Procambarus clarkii: Focus on muscle development and antioxidant - Sharifi Saifullah; Pu Wang; Jin Cen; Yong Cheng; Ejaz Naqeebullah; Bo Liu; Bo Liu; Hongyan Tian; Xiaochuan Zheng; Cunxin Sun (Aquaculture, 2027)

Experimental measurements and modelling of the CO2 solubility in L-lysine co-promoted CESAR-1 (Bio-CESAR) solutions - Saifullah Nasrullah; Richard Obaseki; Danial Qadir; Humbul Suleman; Faizan Ahmad; Nick Tann; Ben Dannatt (Fuel, 2026)

Integrative analysis of single nucleotide polymorphism of PDE7B (rs2327669) with biopsychosocial and biochemical parameters in β-thalassemia major patients in Pakistani Cohort - Faiza Usmani; Muhammad Zohaib Yaseen; Arshi Ali; Mahrukh Nasir; Saifullah (Molecular Biology Reports, 2026)

Synergistic Anticancer effects of Fagonia indica Extract in Combination with Paclitaxel and Benzoporphyrin Derivative - Saba Naz; Ahmat Khurshid; Syed Mujtaba ul Hassan; Adnan Saifullah; Aleena Zahid; Bushra Aziz (Journal of Pharmaceutical Innovation, 2026)

Facile synthesis of cobalt-iron layered double hydroxide and its derived mixed metal oxide for Congo red and Pb(II) remediation - Ramzan Akhtar; Adil Khan; Maria Gul; Mohsin Ali Raza Anjum; Iqra Rafique; Muhammad Rehan; Rashid Nazir Qureshi; Sajid Iqbal; Muhammad Saifullah (Colloids and Surfaces C: Environmental Aspects, 2026)

Enhancement of coconut shell pyrolysis bio-oil functionality via pretreatment: Dewaxing-delignification severity and sequence effects - Alien Abi Bianasari; Minh Thang Le; Dieni Mansur; Saepurahman; Fairuzeta Hj Md Ja'afar; Saifullah Abu Bakar; Quentin Cheok; Abul Kalam Azad (Bioresource Technology Reports, 2026)

Adaptation of wild-type rabies virus on vaccine producing cell line and its quantification by peroxidase-based immunostaining - Muhammad Rehan Riaz; Syed Muhammad Kamran Ullah; Muhammad Rashid; Kaleem Ullah; Hamid Ahmad; Qari Muhammad Kaleem; Faiza Jamil; Saifullah Khan (Archives of Virology, 2026)

A hybrid Wavelet–EfficientNetV2–Vision transformer framework for multiclass brain tumor MRI classification - Oussama Abda; Hilal Naimi; Mohammed Bourennane; Shoffan Saifullah (Physical and Engineering Sciences in Medicine, 2026)

Optogenetic Pacemaker Cells for Biological Cardiac Rhythm Management in Sick Sinus Syndrome - Versha Devi; Syeda Aliza Aamir; Syed Abdullah Shah; Muhammad Dawood Ghaffar; Muhammad Talha; Muneeb Saifullah (Cell Biochemistry and Biophysics, 2026)

Appraising aquifer storage recovery (ASR) for irrigation potential in a coastal environment - Md.Helal Ahmmed; Md.Sabbir Hossain; Sara Nowreen; Md. Moniruzzaman; A.H.M. Shofiul Islam Molla Jamal; Mohammad Moniruzzaman; Iffat Jahan Shammee; Ratan Kumar Majumder; Afroza Sharmin; Shahrina Akhtar; Nabanita Chowdhury; Saifullah Sayed (Journal of Hydrology, 2026)

Latex-modified concrete: a comprehensive review of types, mechanical performance, and durability - Mehtab Ahmad; Saifullah Arabzai; Hanif Ullah; Ali Odeh; Amin Al-Fakih (Innovative Infrastructure Solutions, 2026)

Synergistic Effects of Biochar with Phosphorus Fertilization on soil Biochemical Properties and Wheat Productivity - Nighet Musa; Khalid Saifullah Khan; Muhammad Azeem; Mah-Noor Azad; Mehnoor Khan; Nabeeha Javed; Tajwar Alam (Journal of Soil Science and Plant Nutrition, 2026)

Foliar application of silicon alleviates adverse effect of drought stress by improving growth, physiological attributes, and antioxidant defense of camelina (Camelina sativa L.) - Bilal Ahmad Shahzad; Ejaz Ahmad Waraich; Muhammad Saleem; Saddam Hussain; Saifullah (Acta Physiologiae Plantarum, 2026)

Diagnosing irreducible uncertainty for adaptive environmental management: A transferable framework from wetland fisheries - Md. Saifullah Bin Aziz; Seikh Razibul Islam; Md. Mostafizur Rahman Mondol; Mobin Hossain Shohan; Md. Mehedi Alam; Mohammad Mahfujul Haque (Ambio, 2026)

Assessment of heavy metals and proximate composition of a jellyfish (Rhizostoma octopus Gmelin, 1791) from Cox's Bazar coast, Bay of Bengal, Bangladesh: Tracing contamination sources and human health risks - Md. Simul Bhuyan; Debasish Pandit; Mohammad Ismail; Mir Mohammad Ali; Md Khalid Saifullah; Md. Tarikul Islam; Ahmed Harun-Al-Rashid; Ummey Hafsa Bithi; Mrityunjoy Kunda; Md. Abu Bakar Siddique (Marine Pollution Bulletin, 2026)

New frontiers in beverage fortification: Delivery of functional ingredients via micro- and nanoencapsulation in dairy and non-dairy beverages - Mohammad Rezaul Islam Shishir; Suliman Khan; Naymul Karim; Muhammad Bilal; Sarfaraz Hussain; Md Saifullah; Ahmed K. Rashwan; Haroon Elrasheid Tahir; Isam A. Mohamed Ahmed; Xinhua Zhang; Fujun Li (Food Research International, 2026)

Effects of Dietary Tryptophan on Growth Performance, Muscle Development and Quality, Gut Microbiota of Juvenile Procambarus clarkii - Ying Chen; Ling Zhu; Hanwu Wu; Yebing Yu; Xiaochuan Zheng; Bo Liu; Cunxin Sun; Xuwen Bing; Hongyan Tian; Ejaz Naqeebullah; Sharifi Saifullah; Yongfeng Zhao; et al. (Fishes, 2026)
This study aimed to investigate the effects of dietary tryptophan (Trp) on growth performance and muscle quality of Procambarus clarkii. Six experimental diets with graded Trp concentrations (0.05%, 0.13%, 0.29%, 0.43%, 0.56%, 0.69%; designated Trp0.05 to Trp0.69) were fed to crayfish for 8 weeks. Growth parameters, muscle proximate composition, texture, histology, related gene expression, and intestinal microbiota were measured. Compared with the Trp0.05 group, the Trp0.43 group significantly increased FW, WGR, SGR, and muscle crude protein content, while decreasing FCR. It also improved muscle texture (hardness, springiness, cohesiveness, gumminess, chewiness), increased muscle fiber diameter, and reduced fiber density and the proportion of fibers

Corrigendum to “global research on the air quality status in response to the electrification of vehicles” [Science of the Total Environment, 795, (2021), 148861] - Yansong Bao; Khalid Mehmood; Saifullah; Muhammad Yaseen; Saad Dahlawi; Muhammad Mohsin Abrar; Shah Fahad (Science of The Total Environment, 2026)

Synthesis of biocompatible novel multi-tailed indole-based resorcinarene for effective delivery of quercetin against multidrug-resistant S. aureus - Khadija Rehman; Tasmina Kanwal; Muhammad Hasnain; Rukesh Maharjan; Wajeeha Muzafar; Komal Rao; Salim Saifullah; Shabana Usman Simjee; Muhammad Raza Shah (Archives of Microbiology, 2026)

Fluorine in Pharmaceuticals and Synthetic Strategies for Fluorine-Containing Molecules in Anticancer Drug Discovery: A Review - Vivek Kumar; Meenu; M. Shaquiquzzaman; M. Mumtaz Alam; Mymoona Akhter; Darakhshan Parveen; Mohammad Kaleem; Shyama Charan; Md. Khalid Saifullah; Sharba Tasneem (Journal of Fluorine Chemistry, 2026)

Phenol-rich bio-oil synthesis via single and dual metal-oxide/zeolite catalysts in biomass catalytic pyrolysis: Comparison of Y2O3/ZSM-5 and MgO/Y2O3/ZSM-5 - Alien Abi Bianasari; Minh Thang Le; Muhammad Saifullah Abu Bakar; Saepurahman; Dieni Mansur; Fairuzeta Hj Md Ja'afar; Quentin Cheok; Abul Kalam Azad (Biomass and Bioenergy, 2026)

Sustainable materials for electric vehicle batteries: A comprehensive review of progress, challenges, and opportunities - Noor Hafidzah Jabarullah; Muhammad Saifullah Abu Bakar; Teguh Kurniawan; Asep Bayu Dani Nandiyanto; Asim Laeeq Khan; Fatin Amanina Azis; Muhammad Roil Bilad (Next Research, 2025)

Recirculating aquaculture systems: Advances, impacts, and integrated pathways for sustainable growth - Zubair Hashmi; Faizah Metali; Muhamad Amin; Muhammad Saifullah Abu Bakar; Yusuf Wibisono; Wahyunanto Agung Nugroho; Muhammad Roil Bilad (Bioresource Technology Reports, 2025)

Diet Preference of Orcaella Brevirostris (Irrawaddy Dolphin) from the Bay of Brunei, as Indicated by Stable Isotope Analysis - Mohd Ikram Zuraini; Siti Tafzil Meriam Sheikh Abdul Kadir; Saifullah A. Jaaman; Zulqarnain Mohamed; Xuelei Zhang; Azharuddin Abd. Aziz; Margot Serrurier-Arabadjieva; Maizah M. Abdullah (Thalassas: An International Journal of Marine Sciences, 2025)

The extent of destructive fishing gear use in Bangladesh: Ecological impacts and strategic roadmap for sustainable fisheries management - Md. Mehedi Alam; Md. Saifullah Bin Aziz; Mohammad Mahfujul Haque (Marine Policy, 2025)

Type II toxin-antitoxin systems as stress-responsive survival circuits in archaea and bacteria - Md Rasel Uddin; Saifullah Saifullah (Archives of Microbiology, 2025)

Effects of dietary copper on growth performance, immune responses, and intestinal microbiome in sub-adult crayfish (Procambarus clarkii) - Ejaz Naqeebullah; Bo Liu; Zheng Xiaochuan; Sharifi Saifullah; Chen Ying; Xu Feifan; Aimin Wang (Aquaculture International, 2025)

Assessing the Diversity of Decapods (Crustacea: Malacostraca) With Environmental DNA ( eDNA ) in Coastal Water of Matang, Perak, Malaysia - Chuan‐Hui Lim; Sze‐Looi Song; Zulqarnain Bin Mohamed; Muhammad Fadhli Mat Sobri; Azmi Marzuki Muda; Saifullah Arifin Jaaman (Marine Ecology, 2025)
Decapods play vital ecological and economic roles, yet their diversity and distribution in the coastal waters of Matang remain poorly understood. Increasing anthropogenic pressures have further impacted their habitats, underscoring the need for improved biodiversity assessments. Conventional monitoring methods are often limited by inconsistencies, invasiveness, low taxonomic resolution, and inefficiency in complex habitats. This study evaluated the effectiveness of environmental DNA (eDNA) metabarcoding to assess decapod diversity in Matang waters. A total of 136 seawater samples were collected from predefined zones between October 2021 and October 2022. DNA was extracted using the CTAB method, and a partial mitochondrial cytochrome c oxidase subunit 1 (COI) gene region was amplified. The amplicons were sequenced using the Illumina MiSeq platform. This approach identified 12 decapod species from six families: Penaeidae (3 species), Lucideridae (1 species), Sergestidae (3 species), Dotillidae (1 species), Pilumnidae (1 species), and Diogenidae (3 species). Dominant species included Acetes japonicus (46%), Acetes indicus (27%), and Diogenes fasciatus (10.9%). Notably, eight species matched records from previous conventional surveys, while four additional taxa: 2 Diogenes spp. ( Diogenes fasciatus , Diogenes rectimanus ), a Dotillidae crab ( Ilyoplax serrata ), and a Pilumnidae crab ( Aniptumnus sp.) were newly detected in the area. These findings indicate that decapod richness in Matang is likely underestimated. In summary, eDNA metabarcoding offers a promising, non‐invasive alternative for biodiversity monitoring in dynamic environments and complements traditional methods. This study establishes a foundation for long‐term decapod monitoring and supports conservation efforts in the Matang region.

Seasonal and interannual variability of Karakoram glacier surface albedo from AVHRR-MODIS data, 1982–2020 - Fuming Xie; Shiyin Liu; Tobias Bolch; Yu Zhu; Yongpeng Gao; Shucheng Tan; Muhammad Mannan Afzal; Adnan A. Tahir; Yiyuan Shen; Jinyue Wei; Kunpeng Wu; Muhammad Saifullah (Global and Planetary Change, 2025)

Advancements in photobioreactor systems: Optimizing operations for enhanced microalgal growth and bioremediation - Zubair Hashmi; Ibrahim Maina idriss; Juliana Zaini; Muhammad Saifullah Abu Bakar; Muhammad Roil Bilad (Algal Research, 2025)

Documentation of major pests and spectrum of pesticide usage for tea agroecosystems in Bangladesh - Md. Abdul Maleque; A. F. M. Saiful Islam; Md. Moudud Ahmod; Md. Simon Islam; Rashidul Hasan; Kazi Noor-E-Alam Jewel; Md. Saifullah; H. Roaki Ishii (Agroforestry Systems, 2025)

Volatilomics in meat research: Species authentication, quality assessment & adulteration detection - Zubayed Ahamed; Md Saifullah; Robert A. Shellie; Roger A. Stanley (Food Research International, 2025)

Exploring the propagation characteristics from meteorological to hydrological drought across diverse climate regions in the upper Indus Basin, Pakistan - Arif Hussain; Jianxia Chang; Azfar Hussain; Zhou Kai; Guibin Yang; Muhammad Saifullah (Natural Hazards, 2025)

Cold plasma and integrated approaches for fresh produce preservation: Mechanisms, quality attributes, challenges, and future directions - Mohammad Rezaul Islam Shishir; Md Mostafa Kamal; Naymul Karim; Md Saifullah; Suliman Khan; Ke Zhang; Gobinath Marappan; Halah Aalim; Sulafa B.H. Hashim; Xiaodong Zhai; Li Zhihua; Haroon Elrasheid Tahir; et al. (Trends in Food Science & Technology, 2025)

Transforming agriculture with vermicompost: 7-year empirical evidence from drought-prone and salinization-affected regions of Bangladesh - Md Lokman Hossain; Khusnur Jahan Shapna; Jianfeng Li; Md Humayain Kabir; Farzana Siddika; Saifullah Khandker; Carl Beierkuhnlein (Journal of Cleaner Production, 2025)

Nanosilica-modified binder in porous asphalt under varied ageing conditions - Khairil Azman Masri; Ramadhansyah Putra Jaya; Ahmad Kamil Arshad; Mohamad Saifullah Samsudin; Mohd Rosli Mohd Hasan (Innovative Infrastructure Solutions, 2025)

Dual-layer flat sheet membrane from waste cellulose acetate for natural organic matter removal from surface water - Ibrahima Maina Idriss; Zubair Hashmi; Norazanita Shamsuddin; Muhammad Saifullah Abu Bakar; Sutarat Thongratkaew; Kajornsak Faungnawakij; Yusuf Wibisono; Muhammad Roil Bilad (Journal of Water Process Engineering, 2025)

Seasonal Variations in Potable Water Quality of Bahawalpur City: A Comprehensive Assessment of Major Ions, Organic Matter, and Disinfection Byproducts - Sundas Kali; Mazhar Iqbal Zafar; Abida Farooqi; Muhammad Saifullah; Sajida Rasheed; Muhammad Bilal khan Niazi; Amir Waseem; Luiza C. Campos (Environmental Monitoring and Assessment, 2025)

Developing a method to estimate aerosol generation during poultry slaughtering and defeathering in Bangladesh: An experimental study - Nadia Ali Rimi; Md. Habibullah Fahad; Andrew Clark; Rebeca Sultana; Kamal Hossain; Md. Khaled Saifullah; Ireen Sultana Shanta; David E. Swayne; Md. Zakiul Hassan; Syed Mohammad Golam Mortaza; Sayeda Tasnuva Swarna; Md. Giasuddin; et al. (Building and Environment, 2025)

Biochars Induced Changes in CO2 Evolution and Biochemical Properties of an Alkaline Subtropical soil - Tayyba Kanwal Choudhary; Khalid Saifullah Khan; Qaiser Hussain; Muhammad Ashfaq; Choudhary Muhammad Saqlain (Journal of Soil Science and Plant Nutrition, 2025)

A Novel Optimized Vibration-based Energy Harvester for Leak Detection in Wall-mounted Water Pipelines - Muhammad Faizan Mysorewala; Mati-Ur-Rasool Ashraf Virk; Mujahid Naqeebuddin Syed; Abdul-Wahid Saif; Lahouari Cheded; Saifullah Shafiq; Karim Sattar (Water Resources Management, 2025)

Multi-scale computational modeling to identify novel chemical scaffolds as trehalose-6-phosphate phosphatase inhibitors to combat Burkholderia pseudomallei - Sara Noor; Mohammad Abdullah Aljasir; Maryam Bashir; Kalsoom Khan; Sajjad Ahmad; Syed Ainul Abideen; Saifullah Khan; Farhan Siddique; Hamza Ahmad; Khudija Ghani; Madiha Iqbal; Muhammad Irfan; et al. (In Silico Pharmacology, 2025)

Cardioprotective Potential of d-limonene against Isoproterenol induced Myocardial Infarction in Rats - Md. Saifullah; Tarique Mahmood; Farogh Ahsan; Shahzadi Bano; Syed Mehdi Hasan Zaidi; Mohd Masih Uzzaman Khan (Cell Biochemistry and Biophysics, 2024)

Quantitative assessment of Cd sources in rice grains through Cd isotopes and MixSIAR model in a typical e-waste dismantling area of Southeast China - Kang Tian; Qiang Liang; Yue He; Jingxuan Ma; Tiantian Zhao; Qiumei Wu; Wenyou Hu; Biao Huang; Khalid Saifullah Khan; Ying Teng (Science of The Total Environment, 2024)

Effects of light color on growth, nutrient uptake, and harvesting of the indigenous strain of Chlorococcum sp. - Zubair Hashmi; Juliana Zaini; Rosnah Abdullah; Muhammad Saifullah Abu Bakar; Muhammad Roil Bilad (Bioresource Technology Reports, 2024)

Impact of Rice Husk Biochar on Soil Properties and Microbial Diversity for Paddy Cultivation - Anis Nadiah Abdillah; Pooja Shivanand; Quentin Cheok; Saifullah Abu Bakar; Hussein Taha; Faizah Metali (Journal of Soil Science and Plant Nutrition, 2024)

Underpinning the criteria for the sustainability assessment of Hakaluki Haor using the RAPFISH tool - Md. Saifullah Bin Aziz; Md. Mostafizur Rahman Mondol; Md. Mehedi Alam; Mohammad Mahfujul Haque; Seikh Razibul Islam (Fisheries Research, 2024)

Micro and nano-encapsulated natural products in yogurt: An emerging trend to achieve multifunctional benefits in product quality and human health. - Mohammad Rezaul Islam Shishir; Md Saifullah; Sulafa B.H. Hashim; Halah Aalim; Muhammad Bilal; Suliman Khan; Gobinath Marappan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Muhammad Arslan; Farah Saleena Taip; et al. (Food Hydrocolloids, 2024)

Multi-medium residues and ecological risk of herbicides in a typical agricultural watershed of the Mollisols region, Northeast China - Hanqiang Liu; Rui Li; Wenyou Hu; Le Jian; Biao Huang; Ya'nan Fan; Yongcun Zhao; Hongyan Zhang; Khalid Saifullah Khan (Science of The Total Environment, 2024)

A comprehensive scenario of heavy metals pollution in the rivers of Bangladesh during the last two decades - Debasish Pandit; Mohammad Mahfujul Haque; Md. Simul Bhuyan; Ahmed Harun-Al-Rashid; Partho Protim Barman; Rana Roy; Bishwajit Sarker; Md. Khalid Saifullah; Mrityunjoy Kunda (Environmental Science and Pollution Research, 2024)

Identification of provenance of Basmati rice grown in different regions of Punjab through multivariate analysis - Muhammad Saifullah; Awais Nisar; Ramzan Akhtar; Syed M. Husnain; Shamila Imtiaz; Bashir Ahmad; Munib Ahmed Shafique; Saira Butt; Muhammad Arif; Abid Majeed Satti; Muhammad Shahzad Ahmed; Simon D. Kelly; et al. (Food Chemistry, 2024)

Zinc Provisioned Enhancement of Manganese Use Efficiency Results in Differential Biomass and Grain Production in Two Rice Cultivars Grown in Clay Loam Soil - Faisal Nadeem; Rashid Mahmood; Muhammad Anwar-ul-Haq; Muhammad Sabir; Saifullah; Qingxu Ma; Chongwei Jin; Tayyaba Samreen; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Novel polynomial Abet data augmentation algorithm with GRU paradigm for nuclear power prediction - Saifullah Khan; Saeed Ehsan Awan; Yasir Muhammad; Ihtesham Jadoon; Muhammad Asif Zahoor Raja (Annals of Nuclear Energy, 2024)

Improving canopy transpiration model performance by considering concurrent hot and dry conditions - Dianyu Chen; Xiaotao Hu; Xingwu Duan; Daxin Yang; Youke Wang; Xing Wang; Muhammad Saifullah (Agricultural Systems, 2024)

Prediction of drought regulating gene (s) in barley (Hordeum vulgare L.) using express sequence tags (ESTs) through in silico approaches - Muhammad Naveed Shahid; Fatima Maqbool; Saifullah (South African Journal of Botany, 2024)

A novel cloud enabled smart carbon neutral hydroponic setup for stem cutting propagation of tropical tree species - Navod Neranjan; Ahmad Muzakker Khalid; Zakwan Zakaria; Faizah Metali; Muhammad Saifullah Abu Bakar; Hayati Yassin (Computers and Electronics in Agriculture, 2024)

Occurrence, distribution and ecological risk assessment of herbicide residues in cropland soils from the Mollisols region of Northeast China - Rui Li; Wenyou Hu; Hanqiang Liu; Biao Huang; Zhongjun Jia; Feng Liu; Yuguo Zhao; Khalid Saifullah Khan (Journal of Hazardous Materials, 2024)

Integrated application of biochar and chemical fertilizers improves wheat (Triticum aestivum) productivity by enhancing soil microbial activities - Muhammad Abdullah Aziz; Khalid Saifullah Khan; Rabia Khalid; Muhammad Shabaan; Abdulaziz G. Alghamdi; Zafer Alasmary; Mosaed A. Majrashi (Plant and Soil, 2024)

Waste cellulose acetate-based dynamic membrane for NOM-containing river water filtration - Ibrahim Maina Idriss; Nurul Fadillah; Norazanita Shamsuddin; Muhammad Saifullah Abu Bakar; Sutarat Thongratkaew; Kajornsak Faungnawakij; Wahyunanto Agung Nugroho; Yusuf Wibisono; Asep Bayu Dani Nandiyanto; Muhammad Roil Bilad (Journal of Environmental Chemical Engineering, 2024)

Direct scaling of residual displacements for bilinear and pinching oscillators - Mohammad Saifullah; Vinay K. Gupta (Earthquake Engineering and Engineering Vibration, 2024)

Spatiotemporal variability of precipitation concentration in Pakistan - Muhammad Zaman; Muhammad Adnan Shahid; Ijaz Ahmad; Yan‐Jun Shen; Muhammad Usman; Muhammad Imran Khan; Muhammad Saifullah (International Journal of Climatology, 2023)
Precipitation is a meteorological variable that plays a vital role in determining water resources and managing water risks. The intensity and frequency of precipitation extremes have increased in recent years; however, the changes in precipitation regimes across Pakistan remain unclear. This study analysed spatial and temporal changes in the precipitation concentration index (PCI) and concentration index (CI) from 100 meteorological stations across Pakistan from 1981 to 2017. Using innovative trend analysis (ITA) and Pettitt's test, we detected trends and change points in the annual and wet season PCI and CI. Additionally, we examined the relationship between PCI/CI values and latitude and altitude. The results revealed that the CI and PCI ranged between 0.48–0.78 and 10–55, respectively, with higher values being more prevalent in the dry and hot zones of the country. The study established a linear relationship between PCI/CI values, latitude and altitude, with higher values at lower altitudes and a decrease in values from south to north. Most stations presented a significant positive ITA trend for PCI and CI from 1981 to 2017, with a change between 1985 and 1995, indicating an overall increase in heavy precipitation events in the area. These findings are crucial for disaster preparedness, water resource planning, the mitigation of drought and flood risks, and conservation efforts.

Waste-derived nanobiochar: A new avenue towards sustainable agriculture, environment, and circular bioeconomy - Md. Nasir Hossain Sani; Mehedi Amin; Abu Bakar Siddique; Saifullah Omar Nasif; Bhim Bahadur Ghaley; Liya Ge; Feng Wang; Jean Wan Hong Yong (Science of The Total Environment, 2023)

Incorporating dynamic schemes of canopy light extinction coefficient improves transpiration model performance for fruit plantations - Dianyu Chen; Xiaotao Hu; Xingwu Duan; Xinguang Wei; La Zhuo; Xing Wang; Jing Guo; Saifullah Muhammad (Journal of Hydrology, 2023)

Challenges, limitations, and applications of nanofluids in solar thermal collectors—a comprehensive review - Lukman Ahmed Omeiza; Muhammad Abid; Yathavan Subramanian; Anitha Dhanasekaran; Saifullah Abu Bakar; Abul Kalam Azad (Environmental Science and Pollution Research, 2023)

Exploring the Intertwined Nexus between Globalization, Energy Usage, Economic Complexity, and Environmental Quality in Emerging Asian Economies: A Pathway Towards a Greener Future - Muhmmad Asim Rafiq; Abdul Rauf; Saifullah Shakir; Ameer Muhammad Aamir Abbas; Huaping Sun; Saira Abid (Environmental Science and Pollution Research, 2023)

Prediction of land use and land cover changes (LULC) and urban growth analysis in Dhaka Metropolitan Area (DMA) using CA-Markov model and geospatial techniques - Md. Kausar Hossein; Azom Ahmed; Muhammad Jasim Uddin; A.S.M. Saifullah; Md. Abu Hamjalal Babu; Tasrin Sarker (Arabian Journal of Geosciences, 2023)

Screening for antimicrobial residues in poultry eggs in Bangladesh using Charm II radio-receptor assay technique following validation - Darmin Chakma; Md. Maruf Billah Prince; Md. Hedayetul Islam; E. M. Tanvir; Md. Mahamodun Nabi; Wim Reybroeck; James Jacob Sasanya; M. Jahurul Islam; Md. Nazrul Islam; Md. Shahabe Uddin Talukder; Chironjit Kumar Shaha; M. A. Mannan; et al. (Food Additives & Contaminants Part B-Surveillance, 2023)

Unearthing research trends in emissions and sustainable development: Potential implications for future directions - Khalid Mehmood; Saifullah; Xuchun Qiu; Muhammad Mohsin Abrar (Gondwana Research, 2023)

Soil organic carbon sequestration and modeling under conservation tillage and cropping systems in a rainfed agriculture - Sana ur Rehman; Shahzada Sohail Ijaz; Muhammad Ali Raza; Atta Mohi Ud Din; Khalid Saifullah Khan; Shroz Fatima; Taqi Raza; Sajid Mehmood; Amjad Saeed; Muhammad Ansar (European Journal of Agronomy, 2023)

Ultrasound-assisted sustainable and energy efficient pre-treatments, dyeing, and finishing of textiles – A comprehensive review - Mohammad M. Hassan; Khaled Saifullah (Sustainable Chemistry and Pharmacy, 2023)

Knowledge, attitude, and perceptions about cancer genetic testing in clinical practice in Karachi, Pakistan - Shameel Shafqat; Masooma Naseem; Masooma Rana; Zehra Naseem; Warda Ahmed; Muhammad Daniyal Musharraf; Arisha Zaheer; Ahmed Safiullah Shaikh; Muhammad Bazil Musharraf; Mahnoor Niaz; Saifullah Khan; Rabiya Irfan; et al. (Journal of Community Genetics, 2023)

Salt ion mediated changes in biochemical and anatomical characteristics of Brassica napus can be countered with Moringa Leaf extract - Noreen Akhter; Aqsa Noreen; Saima Saifullah; Ali Noman; Muhammad Muslim Shahnaz; Puleng M. Letuma; Abida Kausar; Maham Siddique; Mohamed Hashem; Saad Alamri; Omar Mahmoud Al-zoubi; Muhammad Saleem; et al. (South African Journal of Botany, 2023)

Macroalgae for biomonitoring of trace elements in relation to environmental parameters and seasonality in a sub-tropical mangrove estuary - Mir Talas Mahammad Diganta; A.S.M. Saifullah; Md. Abu Bakar Siddique; Mohammad Mostafa; Md. Shemul Sheikh; Muhammad Jasim Uddin (Journal of Contaminant Hydrology, 2023)

A Survey on Physical Layer Techniques and Challenges in Underwater Communication Systems - Naveed Ur Rehman Junejo; Mariyam Sattar; Saifullah Adnan; Haixin Sun; Abuzar B. M. Adam; Ahmad Hassan; Hamada Esmaiel (Journal of Marine Science and Engineering, 2023)
In the past decades, researchers/scientists have paid attention to the physical layer of underwater communications (UWCs) due to a variety of scientific, military, and civil tasks completed beneath water. This includes numerous activities critical for communication, such as survey and monitoring of oceans, rescue, and response to disasters under the sea. Till the end of the last decade, many review articles addressing the history and survey of UWC have been published which were mostly focused on underwater sensor networks (UWSN), routing protocols, and underwater optical communication (UWOC). This paper provides an overview of underwater acoustic (UWA) physical layer techniques including cyclic prefix orthogonal frequency division multiplexing (CP-OFDM), zero padding orthogonal frequency division multiplexing (ZP-OFDM), time-domain synchronization orthogonal frequency division multiplexing (TDS-OFDM), multiple input multiple output orthogonal frequency division multiplexing (MIMO-OFDM), generalized frequency division multiplexing (GFDM), unfiltered orthogonal frequency division multiplexing (UF-OFDM), continuous phase modulation orthogonal frequency division multiplexing (CPM-OFDM), filter bank multicarrier (FBMC) modulation, MIMO, spatial modulation technologies (SMTs), and orthogonal frequency division multiplexing index modulation (OFDM-IM). Additionally, this paper provides a comprehensive review of UWA channel modeling problems and challenges, such as transmission loss, propagation delay, signal-to-noise ratio (SNR) and distance, multipath effect, ambient noise effect, delay spread, Doppler effect modeling, Doppler shift estimation. Further, modern technologies of the physical layer of UWC have been discussed. This study also discusses the different modulation technology in terms of spectral efficiency, computational complexity, date rate, bit error rate (BER), and energy efficiency along with their merits and demerits.

Improving zinc and iron density and estimated human bioavailability in rice grain through fertilization - Majid Rahim; Khalid Saifullah Khan; Shahzada Sohail Ijaz; Zahid Akram (Arabian Journal of Geosciences, 2023)

Modelling of geomorphological features of fluvial systems in Eromanga Basin and North Sea using 3D seismic attributes - Haris Ahmed Khan; Saifullah Abdul Qadir; Muhammad Jahangir Khan; Faraz Hasan Siddiqui; Mirza Saad Ahsan (Journal of Earth System Science, 2023)

Remediation of Environmental Contaminants Through Phytotechnology - Abdul Latif; Aown Abbas; Javed Iqbal; Muhammad Azeem; Waleed Asghar; Rehmat Ullah; Muhammad Bilal; Muhammad Arsalan; Madeeha Khan; Rizwan Latif; Muhammad Ehsan; Asad Abbas; et al. (Water, Air, & Soil Pollution, 2023)

Prospects of endophytic fungi as a natural resource for the sustainability of crop production in the modern era of changing climate - Saifullah Omar Nasif; Abu Bakar Siddique; Abu Bakar Siddique; Md. Mazharul Islam; Oliul Hassan; Deen Mohammad Deepo; Akbar Hossain (Symbiosis, 2023)

Water Surface Behaviour of Irrawaddy Dolphin Orcaella brevirostris (Owen in Gray, 1866) and Influencing Factors in the Bay of Brunei, Brunei Darussalam - Nurlisa Azizul; Saifullah Arifin Jaaman; Farah Dayana Haji Ismail; Azmi Marzuki Muda; Xuelei Zhang; Hairul Masrini Muhamad; Mohammad Vol Momin; Bohari Abdullah (Journal of Marine Science and Engineering, 2022)
There is limited information on Irrawaddy dolphins (Orcaella brevirostris) in the Bay of Brunei, Brunei Darussalam. This research was carried out from 2016 to 2018 to determine the water surface behaviour of Irrawaddy dolphins in the bay, the relationship between behaviour and abiotic factors and the number of individuals displaying the behaviour. Behavioural categories, i.e., feeding, socializing, and travelling in groups or individually, and water parameters were documented during boat-based line transect surveys. “Feeding” (n = 188) behaviour was the dominant activity exhibited by the dolphins. The chi-square test (χ2) shows that the frequency of feeding, socializing, and travelling to the water depth range is significantly high (p-value = 0.03). Forty-six percent (46%) of all behavioural categories occurred at depths 1.00–5.99 m. The number of individuals displaying “feeding” behaviour has a weak positive relationship with depth (p-value = 0.07), turbidity (p-value = 0.7), sea surface temperature (p-value = 0.9) and salinity (p-value = 0.9). This study may serve as a baseline for future research. It can help in planning conservation projects and management for Irrawaddy dolphins in the Bay of Brunei, Brunei Darussalam.

Impact of Water Regimes on Minimizing the Accumulation of Arsenic in Rice (Oryza sativa L.) - Muhammad Tahir Shehzad; Muhammad Sabir; Saifullah; Abu Bakkar Siddique; Mohammad Mahmudur Rahman; Ravi Naidu (Water, Air, & Soil Pollution, 2022)

Temperature-Dependent Speciation Analysis of Chromium Immobilized in Calcium Hydroxyapatite Matrix - Sajid Iqbal; Yasir Faiz; Messaoud Harfouche; Muhammad Saifullah; Jong-Il Yun (International Journal of Environmental Research, 2022)

The impact of COVID-19 pandemic on air pollution: a global research framework, challenges, and future perspectives - Khalid Mehmood; Sana Mushtaq; Yansong Bao; Saifullah; Sadia Bibi; Muhammad Yaseen; Muhammad Ajmal Khan; Muhammad Mohsin Abrar; Zaid Ulhassan; Shah Fahad; George P. Petropoulos (Environmental Science and Pollution Research, 2022)

The Morphologies of Mudskipper Pelvic Fins in Relation to Terrestrial and Climbing Behaviour - Saifullah Hidayat; Adhityo Wicaksono; Anita Raharjeng; Desmond Soo Mun Jin; Parvez Alam; Bambang Retnoaji (Proceedings of the Zoological Society, 2022)

Water deficiency with nitrogen enrichment makes Wedelia trilobata to become weak competitor under competition - A. Azeem; J. Sun; Q. Javed; K. Jabran; M. Saifullah; Y. Huang; D. Du (International Journal of Environmental Science and Technology, 2022)

Pollution characteristics and human health risk assessments of toxic metals and particle pollutants via soil and air using geoinformation in urbanized city of Pakistan - Khalid Mehmood; Yansong Bao; Roman Abbas; Saifullah; George P. Petropoulos; Hamaad Raza Ahmad; Muhammad Mohsin Abrar; Adnan Mustafa; Alwaseela Abdalla; Katia Lasaridi; Shah Fahad (Environmental Science and Pollution Research, 2021)

Prediction of changes in water balance of Nam Co Lake under projected climate change scenarios - Muhammad Adnan; Shichang Kang; Muhammad Saifullah; Shiyin Liu; Guoshuai Zhang; Qiudong Zhao; Muhammad Abrar Faiz; Muhammad Zaman (Hydrological Sciences Journal, 2021)

Nutrient Availability to Maize Crop (Zea mays L.) in Biochar Amended Alkaline Subtropical Soil - Tayyba Kanwal Choudhary; Khalid Saifullah Khan; Qaiser Hussain; Muhammad Ashfaq (Journal of Soil Science and Plant Nutrition, 2021)

Carbon-Based Slow-Release Fertilizers for Efficient Nutrient Management: Synthesis, Applications, and Future Research Needs - Muhammad Rashid; Qaiser Hussain; Khalid Saifullah Khan; Mohammad I. Alwabel; Rifat Hayat; Muhammad Akmal; Shahzada Sohail Ijaz; Sarosh Alvi; Obaid-ur-Rehman (Journal of Soil Science and Plant Nutrition, 2021)

Joint low-rank prior and difference of Gaussian filter for magnetic resonance image denoising - Zhen Chen; Zhiheng Zhou; Saifullah Adnan (Medical & Biological Engineering & Computing, 2021)

Soil nutrient status and crop productivity after 6 years of conservation tillage in a subtropical dryland - Sana ur Rehman; Shahzada Sohail Ijaz; Khalid Saifullah Khan; Muhammad Ansar; Qaiser Hussain (Arabian Journal of Geosciences, 2021)

Sulfur Distribution and Availability in Alkaline Subtropical Soils Affected by Organic Amendments - Kouser Majeed Malik; Khalid Saifullah Khan; Mohammad Saleem Akhtar; Zammurad Iqbal Ahmed (Journal of Soil Science and Plant Nutrition, 2020)

Identification of irrigation potential areas, using multi-criteria analysis in Khyber District, Pakistan - Muhammad Waleed; Sajid Rashid Ahmad; Muhammad Asif Javed; Saifullah Samiullah (Environmental Science and Pollution Research, 2020)

Chemical fractionation and risk assessment of trace elements in sewage sludge generated from various states of Pakistan - Umair Riaz; Ghulam Murtaza; Saifullah; Muhammad Farooq; Humera Aziz; Ayesha Abdul Qadir; Shahzada Munawar Mehdi; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Modes of occurrence of calcrete and dolocrete horizons within the Miocene Lower Fars Formation in North Kuwait - Afrah H. Al-Ibrahim; Fikry I. Khalaf; Saifullah K. Tanoli; Ali G. Najem (Arabian Journal of Geosciences, 2020)

High‐frequency whistles of Irrawaddy dolphins ( Orcaella brevirostris ) recorded in Brunei Bay - Ying Jiang; Zongwei Liu; Chunmei Yang; Lian‐gang Lü; Xiaolin Yu; Longfei Huang; Xuelei Zhang; Zhiguo Yang; Guangbing Yang; Lu Sun; Saifullah Arifin Jaaman; Azmi Marzuki Muda (Marine Mammal Science, 2020)
Studies of the whistles of Irrawaddy dolphins ( Orcaella brevirostris ) have traditionally been restricted to analyses of the human audio range (below 20 kHz). In this study, broadband acoustic recordings of Irrawaddy dolphins in Brunei Bay were obtained using a sampling frequency of 512 kHz. Among the 984 whistles collected, eight (0.81%) high‐frequency whistles were detected with fundamentals above 18.4 kHz, which is the reported maximum frequency. Four (50%) of these whistles had the entire fundamentals in the ultrasonic frequency range (above 20 kHz), where 52.3 kHz was the maximum frequency. This is the first description of the ultrasonic components of Irrawaddy dolphin whistles. Our findings demonstrate that the whistles of Irrawaddy dolphins span a wider frequency range than previously published.

A new approach to extend the storage of donor corneas after 28 days of corneal culture in an Italian eye bank - Raffaela Mistò; Jana D’Amato Tóthová; Saifullah Khan; Anna Limongelli; Francesca Pateri (Cell and Tissue Banking, 2020)

Feedstock-induced changes in composition and stability of biochar derived from different agricultural wastes - Tayyba Kanwal Choudhary; Khalid Saifullah Khan; Qaiser Hussain; Munir Ahmad; Muhammad Ashfaq (Arabian Journal of Geosciences, 2019)

Impact of biochar prepared from leaves of Populous euphratica on soil microbial activity and mung bean (Vigna radiata) growth - Muhammad Akmal; Tanveer Ahmed Gondal; Khalid Saifullah Khan; Qaiser Hussain; Mukhtar Ahmad; Muhammad Subtain Abbas; Hafeez Ullah Rafa; Shahab Ahmad Khosa (Arabian Journal of Geosciences, 2019)

Carbon mineralization in subtropical dryland soil amended with different biochar sources - Sehar Sultan; Khalid Saifullah Khan; Muhammad Akmal; Zammurad Iqbal Ahmed; Qaiser Hussain; Shahab Ahmad Khosa (Arabian Journal of Geosciences, 2019)

Reducing Burst Release Effect of Freely Water-Soluble Drug Incorporated into Gastro-Floating Formulation Below HPMC Threshold Concentration Through Interpolymer Complex - Syaiful Choiri; T. N. Saifullah Sulaiman; Abdul Rohman (AAPS PharmSciTech, 2019)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Dual Drugs Anticancer Nanoformulation using Graphene Oxide-PEG as Nanocarrier for Protocatechuic Acid and Chlorogenic Acid - Saifullah Bullo; Kalaivani Buskaran; Rabia Baby; Dena Dorniani; Sharida Fakurazi; Mohd Zobir Hussein (Pharmaceutical Research, 2019)

Quantitative assessment of human health risk posed with chromium in waste, ground, and surface water in an industrial hub of Pakistan - Khalid Mehmood; Hamaad Raza Ahmad; Saifullah (Arabian Journal of Geosciences, 2019)

Stoichiometry of the soil microbial biomass in response to amendments with varying C/N/P/S ratios - Khalid Saifullah Khan; Rainer Georg Joergensen (Biology and Fertility of Soils, 2019)

Integrated use of biochar and compost to improve soil microbial activity, nutrient availability, and plant growth in arid soil - Muhammad Akmal; Zubaira Maqbool; Khalid Saifullah Khan; Qaiser Hussain; Shahzada Sohail Ijaz; Muhammad Iqbal; Irfan Aziz; Amjad Hussain; Muhammad Subtain Abbas; Hafeez Ullah Rafa (Arabian Journal of Geosciences, 2019)

Response of soil microbial biomass and enzymatic activity to biochar amendment in the organic carbon deficient arid soil: a 2-year field study - Muhammad Irfan; Qaiser Hussain; Khalid Saifullah Khan; Muhammad Akmal; Shahzada Sohail Ijaz; Rifat Hayat; Azeem Khalid; Muhammad Azeem; Muhammad Rashid (Arabian Journal of Geosciences, 2019)

Preliminary analysis of echolocation signals produced by fleeing Irrawaddy dolphins (Orcaella brevirostris) - Ying Jiang; Xuelei Zhang; Zhiguo Yang; Saifullah Arifin Jaaman; Qinzeng Xu; Azmi Marzuki Muda; Hairul Masrini Muhamad (Acta Oceanologica Sinica, 2019)

Strategic use of water: a step toward cadmium-free basmati rice (Oryza sativa L.) - Muhammad Naveed; Saifullah; Umair Riaz; Ghulam Murtaza; Sadia Bibi; Ammara Arooj; Qamar uz Zaman (Paddy and Water Environment, 2018)

A field study investigating the potential use of phosphorus combined with organic amendments on cadmium accumulation by wheat and subsequent rice - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Asif Naeem; Balal Yousaf; Guijian Lui; Hinnan Khalid; Saifullah; Farhan Hafeez; Muhammad Azhar (Arabian Journal of Geosciences, 2018)

Factors influencing the behaviour of Irrawaddy dolphins Orcaella brevirostris (Owen in Gray, 1866) in Brunei Bay, Malaysia - Anisul Islam Mahmud; Saifullah Arifin Jaaman; Azmi Marzuki Muda; Hairul Masrini Muhamad; Xuelei Zhang; Felicita Scapini (Journal of Ethology, 2018)

Comparison of the rookery connectivity and migratory connectivity: insight into movement and colonization of the green turtle (Chelonia mydas) in Pacific–Southeast Asia - Hideaki Nishizawa; Juanita Joseph; Yee Kuen Chong; Syed Abdullah Syed Kadir; Irwan Isnain; Tonny Anak Ganyai; Saifullah Jaaman; Xuelei Zhang (Marine Biology, 2018)

Timing of foliar Zn application plays a vital role in minimizing Cd accumulation in wheat - Saifullah; Hina Javed; Asif Naeem; Zed Rengel; Saad Dahlawi (Environmental Science and Pollution Research, 2016)

Poverty within watershed and environmentally protected areas: the case of the indigenous community in Peninsular Malaysia - Fatimah Binti Kari; Muhammad Mehedi Masud; Siti Rohani Binti Yahaya; Md. Khaled Saifullah (Environmental Monitoring and Assessment, 2016)

The antioxidant effect of astaxanthin is higher in young mice than aged: a region specific study on brain - Md. Mamun Al-Amin; Samiha Akhter; Ahmed Tasdid Hasan; Tanzir Alam; S. M. Nageeb Hasan; A. R. M. Saifullah; Mohammad Shohel (Metabolic Brain Disease, 2015)

Status of some fishery resources in a tropical mangrove estuary of Sarawak, Malaysia - Mohammed Muzammel Hoque; Abu Hena Mustafa Kamal; Mohd Hanafi Idris; Osumanu Haruna Ahmed; A.S.M. Saifullah; Md. Masum Billah (Marine Biology Research, 2015)

Sedimentological evidence for the Late Holocene sea level change at the Enjefa Beach exposures of Kuwait, NW Arabian Gulf - Saifullah K. Tanoli (Arabian Journal of Geosciences, 2015)

A biologically based model for recognition of 2-D occluded patterns - Mohammad Saifullah; Christian Balkenius; Arne Jönsson (Cognitive Processing, 2014)

Organic amendments differ in their effect on microbial biomass and activity and on P pools in alkaline soils - Muhammad Asghar Malik; Khalid Saifullah Khan; Petra Marschner; Safdar Ali (Biology and Fertility of Soils, 2013)

Effects of Zn and P addition on the microbial biomass in a Zn deficient calcareous soil amended with glucose - Khalid Saifullah Khan; Rainer Georg Joergensen (Plant and Soil, 2010)

Development of ergosterol, microbial biomass C, N, and P after steaming as a result of sucrose addition, and Sinapis alba cultivation - Khalid Saifullah Khan; Tanja Müller; Jens Dyckmans; Rainer Georg Joergensen (Biology and Fertility of Soils, 2010)

Efficient Plant Genomic and Viral DNA Isolation from Mature Leaf Midrib of Banana (Musa spp) - Ikram-ul-Haq; Saifullah Khan; M. Umar Dahot; Naheed Kousar (Journal of Plant Biochemistry and Biotechnology, 2009)

Aeration volume and photosynthetic photon flux affect cell growth and secondary metabolite contents in bioreactor cultures ofMorinda citrifolia - Saifullah Ahmed; Eun-Joo Hahn; Kee-Yoeup Paek (Journal of Plant Biology, 2008)

Sources of Heavy Metals and Their Long-term Effects on Microbial C, N and P Relationships in Soil - Khalid Saifullah Khan; Krishan Chander; Gerald Hartmann; Norbert Lamersdorf; Rainer Georg Joergensen (Water, Air, & Soil Pollution, 2007)

Comparison of sulfurous acid generator and alternate amendments to improve the quality of saline-sodic water for sustainable rice yields - Munir H. Zia; Abdul Ghafoor; Saifullah; Th. M. Boers (Paddy and Water Environment, 2006)